2011
DOI: 10.4238/2011.november.17.2
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between RANTES-28, SDF-1 gene polymorphisms and systemic lupus erythematosus in the Malaysian population

Abstract: ABSTRACT. Regulated on activation, normal T-cell expressed and secreted (RANTES) and stromal cell-derived factor 1 (SDF-1) are members of the CC-and CXC-chemokine families, respectively. Both genes have been postulated to be involved in the pathogenesis of systemic lupus erythematosus (SLE). We analyzed position 28 of the RANTES gene promoter region, as well as the SNP observed in the 3' UTR of the SDF-1 gene at position 801, in 130 patients presenting SLE at the Malaya University Medical Centre. Screening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…But on the other hand, our results matched studies by Ye et al, Warchol et al, and Lian LH who had genotyped the CXCL12-3′G801A polymorphism in Chinese, Poland, and Malaysian subjects, respectively, and found no association of CXCL12-3′G801A polymorphism with SLE (Ye et al 2005;Warchol et al 2010;Lian et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…But on the other hand, our results matched studies by Ye et al, Warchol et al, and Lian LH who had genotyped the CXCL12-3′G801A polymorphism in Chinese, Poland, and Malaysian subjects, respectively, and found no association of CXCL12-3′G801A polymorphism with SLE (Ye et al 2005;Warchol et al 2010;Lian et al 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Of the remaining publications, 4 review articles and 3 papers with republished data were further excluded. Therefore, we selected 5 eligible publications [ 9 , 10 13 ] on the basis of rigorous inclusion criteria. Among these studies, 3 [ 9 , 10 , 13 ] were carried out in Asians, 1 [ 12 ] focused on Caucasians, and 1 [ 11 ] was involved in Mexican Mestizos.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the important target genes such as C4, C1q, CTLA-4, IL-6, IL-1, RANTES-28, and SDF-1 have been studied previously in the Malaysian population (Puah et al, 2007;Chew et al, 2008;Chua et al, 2009aChua et al, ,b, 2010Lian et al, 2011); however, most of them were found to have no major significant association with SLE susceptibility. Hence in this study, we aimed to target and investigate the distribution of the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) dimorphism and its potential association to the susceptibility of SLE.…”
Section: Introductionmentioning
confidence: 99%